Comparison of aquatic and thera-band exercise on pain, endurance and quality of life among obese people with knee osteoarthritis - Kogilavani S.Krishnan (Tanjong Malim, 2023)
Comparison of aquatic and thera-band exercise on pain, endurance and quality of life among obese people with knee osteoarthritis by Kogilavani S.Krishnan